Molecular mechanistic insight of hepatitis B virus mediated hepatocellular carcinoma - Chaturvedi, Vivek K.; Singh, Anshuman; Dubey, Sushil K.; Hetta, Helal F.; John, James; Singh, M.P. (Microbial pathogenesis, 2019)
Hepatocellular carcinoma (HCC) is a cancer which occurs in liver and severity of this cancer makes it the sixth most prevalent cancer and second leading cause of death among all cancers. The load of hepatitis-B virus (HBV) in serum is one of the important risk factors for the HCC. Several other factors also contribute to the HBV associated malignant hepatoma (HCC) i.e. HBV mutation, integration and condition of the host. Transformation of the liver to HBV-associated HCC usually accompanies long-run symptoms i.e. inflammation and cirrhosis of the liver and infective agent load could be a vigorous prognosticator for each incidence and progression of this carcinoma. One of the prominent factors i.e. HBV X supermolecule (HBx) interferes with many signal pathways that are related to the proliferation and apoptosis of hepatic cells. Besides, HBx C-terminal truncation is also responsible for HCC. Longtime HBV infection causes risk of HCC; thus most of the study related to HBV (85%) is limited to HBV endemic regions. In this review, we have outlined the molecular mechanisms that come from other than HBV endemic places which can be innovative approaches to treat HCC. [Display omitted] •Hepatitis-B virus (HBV) is a para-retrovirus with double-stranded DNA genome, HBVcauses one of the important risk factors for the HCC.•Transformation of the liver to HBV-associated HCC usually accompanies long-run symptoms i.e. inflammation and cirrhosis of the liver and infective agent load could be a vigorous prognosticator for each incidence and progression of this carcinoma.